The Role of Psychological Distress in Relational Health Instability among Romantic Couples: A Qualitative Inquiry - Calda-Tolibas, Michelle A. (The Malaysian Journal of Nursing (MJN), 2022)
Background: Relationship instability, which creates an additional burden to the couples, has contributed to relationship disconnection. Factor like stress plays a vital role in the flux of relationship status and in understanding the stability of intimate relationships and quality in romantic relationships. Yet, there is a dearth on psychological distress noted on non-marital relationship disconnection, since the most documented research has centered on the context of marital bond disconnection. Thus, it prompted the researcher to conduct a qualitative inquiry on the role of psychological distress among women with experiences on mutual bond disconnection. Methods: Constructivist grounded theory and feminist theory designs were utilized to describe the role of psychological distress in relational health instability from the lens of women who participated on this study. This study employed theoretical and purposive sampling methods to enter research interest on relationship loss. Guided by a semi-structured questionnaire, the researcher explored women’s experiences on mutual bond disconnection. However, this paper focused on the thoughts, views, and feelings among women on relational health instability among couples. Results: Thematic analysis generated the participants’ psychological stressors such as disrespect, disinclination, and monetary issues that caused their relational health instability and further led to mutual bond disconnection. Moreover, it provided an in-depth understanding of the factors causing romantic relational health instability such as: (i) humiliation, and (ii) financial matters. Conclusion: The findings provided an increased in-depth understanding of the psychological factors that leads to unhealthy relationships among romantic couples which further cause the mutual bond disconnection.